2014
DOI: 10.30638/eemj.2014.049
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Environmental Impact of Road Pavements From a Life Cycle Perspective

Abstract: The road infrastructure has a major environmental impact by covering important land surfaces and consuming enormous amounts of raw materials for construction and maintenance. The impact of transport pavements needs to be considered from the design stage and to be examined during the whole life cycle of the infrastructure: raw materials extraction and initial transformation, manufacturing, placement on site, exploitation, maintenance, and demolition. This paper evaluates the impact of asphalt and concrete pavem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Particularities such as the pavement conditions and the deterioration over time directly influences the rolling resistance of the pavement, affecting the safety, noise level, CO 2 emissions, and fuel consumption of vehicles [5][6][7][8][9]. Therefore, decisions such as defining the least impactful material to construct urban roads, the pavement design, and the periodicity of interventions have a higher impact on the overall impacts caused by roads [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularities such as the pavement conditions and the deterioration over time directly influences the rolling resistance of the pavement, affecting the safety, noise level, CO 2 emissions, and fuel consumption of vehicles [5][6][7][8][9]. Therefore, decisions such as defining the least impactful material to construct urban roads, the pavement design, and the periodicity of interventions have a higher impact on the overall impacts caused by roads [10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that LCA tools [15,16,[18][19][20][21] can provide a long-term perspective by comparing different solutions and possibilities for urban pavements [10]. However, finding the best materials and structures and an "optimal" maintenance and rehabilitation strategy that can ensure acceptable road conditions, lower agency-user costs, and reduced environmental-social impacts [22] requires complex data analysis and is strongly influenced by local conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For ULS, it should be indicated the higher load carrying capacity, more ductile failure modes and larger energy absorption and dissipation capacity and structural integrity under loading conditions representative of extreme events [1,[9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The fibre reinforcement also provides significant enhancements in the durability [22][23][24][25][26][27][28][29][30] and life cycle of concrete structures [31][32][33][34]. The main applications of FRC are still concentrated in flooring, tunnelling and in some pre-fabrication [1,[35][36][37][38][39][40][41][42][43], being too scarce in the development of innovative structural systems where the benefits of the fibre reinforcement mechanisms have recognized potential for obtaining technical and economic advantages regarding conventional systems.…”
mentioning
confidence: 99%